LEGAL PROTECTION FOR CONSUMERS IN THE SALE AND PURCHASE OF SACRIFICIAL ANIMALS ACCORDING TO ISLAMIC LAW - Jumaika Zwana; Bakri, Nurdin; Abdullah, Muslem (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
This article aims to examine the legal protection for consumers in the sale and purchase of qurban animals provided by Kutaraja Aqiqah as a business actor to its customers (consumers) according to Islamic law. The research method used is qualitative research, namely solving problems by collecting, compiling, analysing, and interpreting the data that has been obtained. The phenomenon that occurs about consumer protection in Kutaraja Aqiqah demands descriptive analysis and answers. This can be fulfilled by describing the conditions and situations, as well as answers related to the problems in the phenomenon. The results of this study conclude that first, the mechanism of buying and selling transactions in kutaraja aqiqah follows the teachings of Islamic law, several types of livestock buying and selling transactions in kutaraja aqiqah such as cash, salam contracts, down payments, and qurban arisan. Second, the form of protection provided by kutaraja aqiqah according to Islamic law is in accordance with sharia which is also beneficial for business actors in attracting the attention and interest of purchasing power of customers